Cost-effectiveness of rezvilutamide versus bicalutamide and androgen-deprivation therapy in patients with highvolume, metastatic, hormone-sensitive prostate cancer - Wu, Huina; Sun, Lei; Feng, Rui; Zhang, Huiyue; Tang, Ke; Wang, Shuo; Nie, Jing (Frontiers in Pharmacology, 2024)
Background Rezvilutamide, a novel androgen-receptor inhibitor with limited blood-brain barrier penetration, exhibits significant antitumour activity against highvolume, metastatic, hormone-sensitive prostate cancer (mHSPC). In this study, we aimed to compare the cost-effectiveness of rezvilutamide and bicalutamide as first-line treatments for untreated prostate cancer among Chinese patients, in order to evaluate the efficacy of rezvilutamide. Methods In this study, we utilized partition survival model to assess the cost-effectiveness of rezvilutamide and bicalutamide treatments for highvolume mHSPC. The model was developed using TreeAge Pro 2022 software and relied on clinical data obtained from the CHART trial. Transition probabilities were estimated from the reported survival probabilities in trials using parametric survival modeling. From the perspective of the Chinese healthcare system, we calculated quality-adjusted life-years (QALYs), incremental cost-effectiveness ratio (ICER), and lifetime cost. A lifetime horizon and an annual discount rate of 5% were employed. To address modeling uncertainties, we conducted one-way sensitivity analysis and probabilistic sensitivity analysis (PSA). Results The cost of rezvilutamide versus bicalutamide were $62681.29 and $13225.73. Rezvilutamide had an ICER of $41891.71 per additional QALYs gained compared with bicalutamide. Research indicated that rezvilutamide achieved at least an 28.20% probability of cost-effectiveness at the threshold of $38223.34/QALY. One-way sensitivity analysis revealed that the results were sensitive to utility of PD. Scenario analysis showed that rezvilutamide was cost-effectiveness if its price was reduced by more than 10%. Conclusions Based on the analysis at the current price, rezvilutamide was found to be less cost-effective for patients with highvolume mHSPC compared to bicalutamide in China.